Fractional laser-assisted topical delivery of bleomycin quantified by LC-MS and visualized by MALDI mass spectrometry imaging - Kristoffer K. Hendel; Charlotte Bagger; Uffe H. Olesen; Christian Janfelt; Steen H. Hansen; Merete Haedersdal; Catharina M. Lerche (Taylor & Francis Group, 2019)
Bleomycin exhibits antiproliferative effects desirable for use in dermato-oncology but topical use is limited by its 1415 Da molar mass. Ablative fractional laser (AFL)-assisted drug delivery has been shown to enhance drug uptake in skin. The aim of this study was with AFL to deliver bleomycin into skin, quantify uptake, and visualize biodistribution with mass spectrometry. In a Franz diffusion cell study, pig skin samples (n = 66) were treated with AFL (λ = 10,600 nm), 5% density, and 0, 5, 20, or 80 mJ/microbeam (mb) pulse energies before exposure to bleomycin for 0.5, 4, or 24 h. Bleomycin was quantified in biopsy cryosections at depths of 100, 500, and 1500 µm using high-performance liquid chromatography-mass spectrometry (LC-MS), and drug biodistribution was visualized for 80 mJ/mb samples by matrix assisted laser desorption/ionization mass spectrometry imaging (MALDI-MSI). The pulse energies 5, 20, and 80 mJ/mb resulted in microscopic ablation zones (MAZs) reaching superficial, mid, and deep dermis respectively. Bleomycin was successfully delivered into the skin and deeper MAZs and longer exposure time resulted in higher skin concentrations. After 24 h, AFL exposure resulted in significant amounts of bleomycin throughout all skin layers (≥510 µg/cm3, p ≤ .002). In comparison, concentrations in intact skin exposed to bleomycin remained below limit of quantification. MALDI-MSI supported the quantitative LC-MS results by visualizing bleomycin biodistribution and revealing high uptake around MAZs with delivery into surrounding skin tissue. In conclusion, topical drug delivery of the large and hydrophilic molecule bleomycin is feasible, promising, and should be explored in an in vivo setting.